COVID-19 Usurps Host Regulatory Networks - Curran, Colleen S.; Rivera, Donna R.; Kopp, Jeffrey B. (Frontiers in Pharmacology, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes coronavirus disease 2019 (COVID-19). SARS-CoV-2 binds the angiotensin-converting enzyme 2 (ACE2) on the cell surface and this complex is internalized. ACE2 serves as an endogenous inhibitor of the renin-angiotensin-aldosterone system (RAAS), the coagulation cascade and the kallikrein-kinin system (KKS). Insight into the pathophysiological effects of SARS-CoV-2 on these pathways is needed, particularly given the current lack of proven, effective treatments. The vasoconstrictive, prothrombotic and pro-inflammatory conditions induced by SARS-CoV-2 can be ascribed, at least in part, to the activation of these intersecting physiological networks. Moreover, patients with hypertension, diabetes, coronary heart disease, and kidney disease often have RAAS pathway activation, either due to underlying disease or to medications, and may be more susceptible to SARS-CoV-2 infection. Certain characteristic COVID-associated skin, sensory, and central nervous system manifestations may also be linked to viral activation of the RAAS, coagulation, and KKS pathways. Pharmacological targets along these pathways may be useful in mitigating symptoms and preventing organ or tissue damage. While more effective anti-viral therapies are critically needed, further study of these pathways may identify effective adjunctive treatments and clarify which patients are most likely to benefit.